2018
DOI: 10.1096/fj.201801489r
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell analyses reveal functional classification of dendritic cells and their potential roles in inflammatory disease

Abstract: Dendritic cells (DCs) have crucial roles in immune‐related diseases. However, it is difficult to explore DCs because of their rareness and heterogeneity. Although previous studies had been performed to detect the phenotypic characteristics of DC populations, the functional diversity has been ignored. Using a combination of flow cytometry, single‐cell quantitative PCR, and bioinformatic analysis, we depicted the DC panorama with not only phenotypic but also functional markers. Functional classification of DCs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The anti-inflammatory macrophage marker CLDN1 (Van den Bossche et al, 2012) and acute-phase inflammation resolution marker ANXA3 (Yamanegi et al, 2018) have been previously reported with distinct macrophage functions. The macrophage scavenger receptor 1 ( MSR1 ) has also been shown to be involved in lipid uptake and migration ability of macrophages (Shi et al, 2019). Three noncoding RNAs ( RF00221 [ snoRD43 ], RF00593 [ snoU83B ], and RF01151 [ snoU82P ] were among genes corresponding to ASE inducible SNVs.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-inflammatory macrophage marker CLDN1 (Van den Bossche et al, 2012) and acute-phase inflammation resolution marker ANXA3 (Yamanegi et al, 2018) have been previously reported with distinct macrophage functions. The macrophage scavenger receptor 1 ( MSR1 ) has also been shown to be involved in lipid uptake and migration ability of macrophages (Shi et al, 2019). Three noncoding RNAs ( RF00221 [ snoRD43 ], RF00593 [ snoU83B ], and RF01151 [ snoU82P ] were among genes corresponding to ASE inducible SNVs.…”
Section: Resultsmentioning
confidence: 99%
“…In normal renal tissue, cDCs constitute the majority, while monocyte‐derived DCs are absent. At such stable state, DCs are mainly immature, with low expression of costimulatory molecules such as CD80 and CD86, suppressing adaptive T‐ and B‐lymphocytes immunity 161 . However, upon infection, pathogen‐associated molecular patterns, damage‐associated molecular patterns (DAMPs) and inflammatory stimuli facilitate activation and maturation of DCs, which subsequently activate renal macrophages and T cells, thus regulating inflammatory responses and renal injury 162 …”
Section: Dcsmentioning
confidence: 99%
“…Receptor expression determines the specificity of kidney DCs. CX3CR1 and CCR2 are incorporated into the action of leaving the bone marrow, and CXCR4 helps precursor DCs retention in the marrow (24)(25)(26). But the inflammatory conditions after transplantation possibly alter the migration mechanism to mediate both rejection and tolerance, which remain unidentified and might be potential intervention sites in the future (Figure 1).…”
Section: Dc-linked Pathological Procedures In Renal Transplantation the Origin And Migration Of Dcs In Kidney Allograft Rejectionmentioning
confidence: 99%
“…With no stimuli, immature kidney DCs inhibit T and B lymphocytes, which also can coordinate tolerance (25). Danger-associated molecular patterns occur when ischemia and reperfusion happen, activating TLR4 (toll-like receptor 4) and leading to the maturation of DCs (27)(28)(29).…”
Section: The Maturation Of Dcs In Kidney Allograft Rejectionmentioning
confidence: 99%